Penerapan Pembelajaran Berbasis Media Puzzle untuk Meningkatkan Kemampuan Kognitif Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMP Negeri 2 Peterongan Jombang - Dwiyanti, Azza Riski; Chotimah, Chusnul (Lembaga Yasin AlSys, 2025)
Islamic Religious Education (PAI) learning at SMP Negeri 2 Peterongan Jombang faces challenges due to low student engagement and cognitive ability, which stem from monotonous and unengaging teaching methods. This study aims to describe the application of puzzle media in PAI learning and to evaluate its impact on improving students' cognitive abilities. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with source triangulation for validation. The findings show that the use of puzzle media creates an interactive, enjoyable, and collaborative learning environment. Students became more active and motivated, showing improved understanding and memory of the material. Cognitive improvement was indicated by successful puzzle completion, enthusiasm during quizzes, and better learning outcomes. The media was found to be easy to make, cost-effective, and effective in enhancing concentration and group cooperation, although it posed limitations such as preparation time, potential errors in arrangement, and uneven participation. These findings suggest that puzzle media is an effective learning strategy to enhance students' cognitive abilities in PAI classes. The implication is that teachers can utilize this media as an innovative alternative to create a more meaningful and engaging learning process.